PENGARUH FAKTOR PENGETAHUAN BISNIS, APLIKASI KEMAJUAN SISTEM, USER SUPPORT, PROGRAMMING, DAN PERENCANAAN SISTEM TERHADAP PENENTUAN PENGEMBANGAN KUALITAS PROFESIONAL DI BIDANG SISTEM INFORMASI AKUNTANSI PADA PERUSAHAAN KONTRAKTOR DI KOTA MANADO - Korompis, Claudia W.M (Universitas Sam Ratulangi, 2014)
After the development of technology, in which the information system is planned on the basis of the computer, the computer becomes a dominant role. Developers sistempun not an accountant, but rather a group of computer programmers who study accounting and then construct a system with the help of the workers in the company's accounting. College as a container in the form of competent personnel who are experts in the accounting information system, should undertake the development of the material accounting information system that can accommodate the need for accounting processes in a dynamic situation at this time. This study aims to determine whether the Business Knowledge, Application Advancement System, User Support, Programming, and Planning System affect the determination of the quality of professional development in the field of accounting information systems contracting company in the city of Manado. The analysis method used is multiple linear regression. The results showed that the variables of business knowledge, Application Advancement System, User Support, Programming, Planning System but less significant effect on the determination of the quality of professional development on the Accounting Information System contractor in the city of Manado.